Hong–Ou–Mandel interferometry and quantum metrology with multimode frequency-bin entangled photons - Xu Jing; Linjie Fan; Xiaodong Zheng; Tangsheng Chen; Yuechan Kong; Bin Niu; Liangliang Lu (APL Photonics)
Quantum entanglement is a vital resource in quantum information processing. High-dimensional quantum entanglement offers advantages that classical systems cannot surpass, particularly in enhancing channel capacity, improving system noise resilience, and increasing sensitivity to external environments. The construction of multimode entanglement in the spectral domain is well-suited for fiber-optic systems. Here, we present a straightforward scheme for generating multimode frequency-bin entanglement using a semiconductor chip through a simple mode conversion. A general model for Hong–Ou–Mandel (HOM) interference with a multimode frequency-bin entangled state is presented and applied to the experiments. The multimode entangled photons we produced exhibit HOM interference with a high-visibility beating pattern, demonstrating a strong relationship with the mode number, mode spacing, and the profile of the single mode. Building on the Fisher information analysis, we explore the relationship between the features in multimode entangled state interference traces and the precision of interferometric measurements even in the presence of experimental nonidealities. This work may deepen the understanding of multimode frequency-bin entanglement and advance the application of multimode HOM interference in quantum sensing.